1996
DOI: 10.1155/1996/21750
|View full text |Cite
|
Sign up to set email alerts
|

‘Latent’ Portal Hypertension in Benign Biliary Obstruction

Abstract: A prospective study was undertaken to evaluate the changes in portal venous pressure in patients with benign biliary obstruction (BBO) but without overt clinical, endoscopic or radiological evidence of portal hypertension. Portal venous pressure was measured at laparotomy in 20 patients (10 each with either benign biliary stricture or choledocholithiasis) before and after biliary decompression. Pressure was found to be on the high side in seven patients (>25 cm of saline in three patients and > 30 cm of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…In a previous study by our group, patients with benign obstructive jaundice, namely PCBDS and choledocholithiasis, were reported to have “latent portal hypertension” that was immediately reversed following relief of biliary obstruction. Liver biopsy showed cholangiohepatitis in the majority of these patients, although no specific grading system was used in that study 8 . On review, with the use of the scoring system in the present study, we observed that all the patients in the previous study did have varying degrees of fibrosis.…”
Section: Discussionmentioning
confidence: 42%
“…In a previous study by our group, patients with benign obstructive jaundice, namely PCBDS and choledocholithiasis, were reported to have “latent portal hypertension” that was immediately reversed following relief of biliary obstruction. Liver biopsy showed cholangiohepatitis in the majority of these patients, although no specific grading system was used in that study 8 . On review, with the use of the scoring system in the present study, we observed that all the patients in the previous study did have varying degrees of fibrosis.…”
Section: Discussionmentioning
confidence: 42%
“…It has also been suggested that periportal fibrosis plays a pivotal role in the development of PH. However, other factors like hepatocyte hyperplasia and increased intraductal biliary pressure are also important . The duration of biliary obstruction is directly related to the reversal of microscopic and hemodynamic changes of PH caused by experimental ligation of the bile duct, and a similar association has been reported in two retrospective studies in humans …”
Section: Introductionsupporting
confidence: 55%
“…However, other factors like hepatocyte hyperplasia and increased intraductal biliary pressure are also important. [8][9][10] The duration of biliary obstruction is directly related to the reversal of microscopic and hemodynamic changes of PH caused by experimental ligation of the bile duct, 11,12 and a similar association has been reported in two retrospective studies in humans. 13,14 We measured the portal pressure (PP) in patients with post-cholecystectomy benign biliary stricture (PCBBS) and assessed its relationship with the injury repair interval (IRI), bile duct pressure (BP), severity of hepatic fibrosis (FS) and other factors.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations